(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
A persistent inflammatory skin condition, psoriasis affects 2% to 4% of the population. About 10% of psoriasis patients develop inflammatory arthritis, which can significantly impair daily activities and life quality. It is also regarded as a psychosomatic illness for which there is no long-term treatment. According to Ayurveda, the patient was diagnosed as having Kapha-pitta dominance, or Ekkustha. The purpose of this case study is to assess the effectiveness of Shaman Chikitsa and Virechan in treating recurring psoriasis. PASI was used to measure symptoms both before and after therapy. There was improvement in the PASI score. The Ayurvedic psoriasis was effectively managed with Shodhan treatment, according to recognized measures.